PENGARUH KEPUTUSAN INVESTASI, KEBIJAKAN DIVIDEN, LEVERAGE DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN - Sari, Maya; Fidiana, Fidiana (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to test the investment decision, dividend policy, leverage and profitability to thefirm value. The population is all consumer goods companies which are listed in Indonesia Stock Exchange in2012-2015 periods. Based on the criteria of purposive sampling, 16 companies with the amount of observation is64 observation have been selected as samples. This research has been carried out by using multiple linearregressions with software of SPSS 23 (Statistical Product and Service Solutions). The result of determinationcoefficient is 90.7% which means that the firm value can be explained by four independent variables and 9.3% offirm value can be explained by other variables which are not included in this research. The result of this researchshows that (1) investment decision gives positive influence to the firm value. (2) Dividend policy gives positiveinfluence to the firm value. (3) Leverage gives positive influence to the firm value. (4) Profitability gives positiveinfluence to the firm value.Keywords: investment decision, dividend policy, leverage, profitability, firm value.